Evaluating the impact of adopting conservation agriculture on farm returns of smallholder vegetable farmers in the Eastern Cape Province: implication for extension services - Qange, Siphesihle; Mdoda, Lelethu; Nontu, Yanga; Mabitsela, Mosima M.; Gidi, Lungile S. (Frontiers in Sustainable Food Systems, 2025)
IntroductionConservation Agriculture provides sustainable practices for reducing costs of production and enhancing soil health, yet adoption rate among smallholder vegetable farmers in South Africa remains inadequate. This study examines the impact of Conservation Agriculture adoption on farm returns in the Eastern Cape and explores implications for extension services.MethodsA mixed-methods approach was employed, using structured questionnaires from 200 smallholder vegetable farmers. Logistic regression and Endogeneity Switching Regression (ESR) model were used for analysis.ResultsLogistic regression identified significant factors influencing adoption, including age, family size, and farm size, education, credit access, market distance and extension services. An Endogeneity Switching Regression (ESR) model revealed that CA adopters attained higher vegetable productivity and income compared to non-adopters. Key challenges to adoption included financial constraints, limited knowledge, inadequate access to resources, and socio-cultural factors.DiscussionThe results highlight the economic benefit of CA and the need for targeted extension support, financial provision such as input subsidies and low-interest credit schemes to ease the financial burden on smallholder farmers, additional structured knowledge dissemination. Future research must investigate the intensity of CA practices across regions and long-term environmental implications.